Posterior cerebral artery stenosis related to implanted intracranial electrodes for temporal lobe epilepsy: A case report. (April 2023) - Matsuda, Daiki; Higashi, Takuichiro; Sato, Masanori; Hosoyama, Hiroshi; Otsubo, Toshiaki; Hanaya, Ryosuke
Abstract: Introduction: Intracranial electroencephalography is a crucial diagnostic technique for epilepsy surgery, though it is associated with a range of complications, including infection, intracranial hemorrhage, increased intracranial pressure, and cerebral infarction. This case study presents an uncommon occurrence of stenosis of the left posterior cerebral artery (PCA) following intracranial electrode implantation. Case presentation: A woman in her thirties with drug-resistant focal impaired awareness seizures underwent implantation of subdural and depth electrodes on the bilateral temporal lobes to lateralize seizure onset. A left anterior-temporal lobectomy was performed based on the evaluation results. Following the resection of the hippocampus, stenosis of the left PCA, with a pinched appearance, was observed. Postoperatively, extensive cerebral edema in the bilateral temporal lobes and a defect in the left PCA were detected on magnetic resonance (MR) imaging. MR imaging performed the day after surgery showed cerebral infarction in the left medial temporal lobe and left lateral thalamus. A video review indicated that surgical manipulation was not the cause of vascular stenosis. MR angiography one week later confirmed the recanalization of the PCA. Discussion: We surmised that the subdural electrodes inserted along the middle skull base might have induced the PCA stenosis or spasms. The patient did not experience any significant sequelae, with no episodes of seizures for more than five years after surgery. Conclusion: It is essential to note that subdural grid electrodes placed in the medial temporal lobe can cause vascular stenosis, albeit with an extremely rare occurrence. Highlights: We reported a severe left PCA stenosis after intracranial electrode implantation. Subdural grid electrodes on the medial temporal lobe could contact PCA. Direct contact of the grid electrode may induce PCA stenosis. In the presence of PCA stenosis, vasospasm can cause severe blood flow reduction. It is important not to induce mechanical vasospasm when PCA stenosis is identified.